Sectoral variability and the foundations of optimal inflation rate. Issue 38 (15th August 2019) - Khan, Muhammad; Eggoh, Jude
ABSTRACT: The recent monetary search models argue that the real effects of inflation on economic activity can be gauged through relative price variability (RPV). Our study uses a large panel data of 32 developed and emerging European economies to test the relationship between inflation and RPV. We use a panel threshold model to explore the regime-specific effects of inflation on RPV. Our results confirm a non-linear profile of the relationship between inflation and RPV. Consistent with the monetary search models, our results show that the effects of inflation on the RPV are more significant in its low (below 0.792% per annum) and high (beyond 2.064% per annum) regimes. Finally, we also report a strong moderating role of central bank independence (CBI) in the inflation–RPV relationship.